PENGARUH PROFITABILITAS DAN STRUKTUR MODAL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA - Nur Indah Alam (Celebes Education Review, 2021)
This study aims to examine and analyze the effect of stock prices on firm value in the manufacturing sector of the food and beverage sub-sector on the Indonesia Stock Exchange. Indonesia. (To test and analyze the simultaneous effect of stock prices and corporate social responsibility (CSR) on firm value in the manufacturing sector of the food and beverage sub-sector on the Indonesia Stock Exchange. The results of the research are (1) 36.2% share price, and corporate social responsibility affects the value of the company in the manufacturing sector of the food and beverage sub-sector on the Indonesia Stock Exchange. (2) Stock prices have a positive and significant effect on firm value in the food and beverage sub-sector manufacturing sector on the Indonesia Stock Exchange. (3) Corporate social responsibility has a positive and significant effect on firm value in the food and beverage sub-sector manufacturing sector on the Indonesia Stock Exchange. (4) Simultaneously or together the variables of stock price, and corporate social responsibility have a significant influence on firm value in the food and beverage sub-sector manufacturing sector on the Indonesia Stock Exchange